2010
DOI: 10.1105/tpc.110.080036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TETRAKETIDE α-PYRONE REDUCTASE Function in Arabidopsis thaliana Reveals a Previously Unknown, but Conserved, Biochemical Pathway in Sporopollenin Monomer Biosynthesis  

Abstract: The precise structure of the sporopollenin polymer that is the major constituent of exine, the outer pollen wall, remains poorly understood. Recently, characterization of Arabidopsis thaliana genes and corresponding enzymes involved in exine formation has demonstrated the role of fatty acid derivatives as precursors of sporopollenin building units. Fatty acyl-CoA esters synthesized by ACYL-COA SYNTHETASE5 (ACOS5) are condensed with malonyl-CoA by POLYKETIDE SYNTHASE A (PKSA) and PKSB to yield a-pyrone polyketi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
215
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 191 publications
(227 citation statements)
references
References 53 publications
12
215
0
Order By: Relevance
“…Since the P450 hydroxylases are likely ER localized, they may form metabolons with the ER-associated PKSs to form alkyl-a-pyrones. Consistent with this, the TKPR1 enzyme that appears to act downstream of PKSA and PKSB is also ER localized (Grienenberger et al, 2010), suggesting the presence of an ER-localized pathway for alkyla-pyrone sporopollenin precursor biosynthesis.…”
Section: Biochemical Functions Of Pksa and Pksbsupporting
confidence: 56%
See 4 more Smart Citations
“…Since the P450 hydroxylases are likely ER localized, they may form metabolons with the ER-associated PKSs to form alkyl-a-pyrones. Consistent with this, the TKPR1 enzyme that appears to act downstream of PKSA and PKSB is also ER localized (Grienenberger et al, 2010), suggesting the presence of an ER-localized pathway for alkyla-pyrone sporopollenin precursor biosynthesis.…”
Section: Biochemical Functions Of Pksa and Pksbsupporting
confidence: 56%
“…In the majority of anthers observed, defective microspore development was first observed at stage 9 (Figure 8), consistent with the timing of transient PKSA and PKSB expression (Figure 3) and protein accumulation (Figure 4) in the tapetum and the timing of exine formation (Blackmore et al, 2007). High-resolution TEM images of stage 9 wild-type and double mutant anthers (Figure 9) showed that mutant microspores completely lacked exine, which was replaced by an amorphous material similar to that we observed in other mutants defective in sporopollenin biosynthesis (acos5, abcg26, and drl1/tkpr1; de Azevedo Souza et al, 2009;Grienenberger et al, 2010;Quilichini et al, 2010). No abnormalities in tapetum cells were observed, and anther epidermal wall cutin deposition was similar to that in wild-type plants.…”
Section: Pksa and Pksb Are Specifically Required For Sporopollenin Bimentioning
confidence: 65%
See 3 more Smart Citations